ANALISIS PERKEMBANGAN PEDAGANG KAKI LIMA DI LINGKUNGAN UNIVERSITAS TANJUNGPURA PONTIANAK - Maspuadi Maspuadi; Witarsa Witarsa; Achmadi Achmadi (Universitas Tanjungpura, 2019)
Abstract This research aims to determine the development of street vendors in Tanjungpura University in Pontianak by looking at the characteristics of street vendors with the approach of 2 (two) aspects, namely economic aspects, and environmental aspects. This research uses a qualitative method with a descriptive approach. Data collection techniques used were observation, interviews and documentation. The data validity checking technique uses triangulation. The results of this research show that: (1) The economic aspects of street vendors selling at the Tanjungpura University in Pontianak, it can be seen that the business capital spent to start a business is not too large or can be classified as small, which is between 3 million and 5 million, while daily venture capital that is spent depends on the availability of goods available while the street vendor's income is also not too basic, for gross income in one day which is around 200 thousand - 300 thousand, while net income is 100 thousand - 150 thousand. The income is only enough to fulfill daily family life.(2) Environmental aspects, street vendors in the University of Tanjungputra Pontianak meet the existing roads on the power road, Sepakat 2 road and in the PBA park, the street vendors are well-organized, neat and comfortable to look at. Another thing to be concerned about is the cleanliness of the environment in which traders sell.Keywords: Development, economic aspects, environmental aspects